Determinants Of Innovative Work Behavior Among White-Collar Workers : A Study Of The Manufacturing Firms Within The Electrical And Electronic (E&E) Sector Of Penang - Lam, Sook Mee (2010)
This study sought to examine the relationship between three categories of predictor variables (organizational, job and personality) and innovative work behavior. Kajian ini bertujuan untuk menguji perhubungan di antara riga kategori variabel penentu (variabel organisasi, variabel pekerjaan, dan variabel personaliti) dengan gelagat ketja inovatif.